Association of Microbiome Metabolite Valerobetaine with Aging. (29th May 2020) - Go, Young-Mi; Liu, Ken; Jarrell, Zachery; Bellissimo, Moriah; Jones, Dean
Abstract: Objectives: The gut microbiome changes with age, and rapamycin treatment both delays aging and modulates the microbiome. This raises important questions concerning cause-effect relationships between microbiome, mTOR signaling and aging mechanisms. Microbiome metabolite valerobetaine (VB) disrupts mitochondrial fatty acid oxidation mechanism. Thus, we tested the hypothesis that increase in VB with aging activates mTORC1 and stimulates lung aging. Methods: Plasma collected from 179 healthy humans (age; 21 to 75) without known disease (CHDWB, Center for Health Discover and Well Being), and lungs from mice (6 mo and 24 mo, n  = 24 each) were analyzed for VB by high resolution metabolomics (HRM). Lung fibroblasts (LF) treated with VB were analyzed for activation of mechanistic target of rapamycin (mTOR) pathway by Western blot analysis. Results: VB concentration in human plasma was significantly increased with age ( P  = 0.0004, r  = 0.26). Consistently, lung VB level in old mice were significantly higher than young mice ( P  = 0.004). LF treated with VB stimulated phosphorylation of mTOR and ribosomal protein S6 as markers for mTORC1 activation, and rapamycin mTORC1 inhibitor substantially decreased VB-stimulated phosphorylation of S6 and mTOR. Conclusions: The results show significant association of VB with aging in human and mouse lung studies, and VB-stimulated mTORC1. The finding suggests that microbiome metabolite VB could impact aging and indicates that studies are needed to understand potential dysfunctions related to age and age-associated diseases such as pulmonary fibrosis. Funding Sources: NIH R01 ES023485 and S10 OD018006.